2002
DOI: 10.1038/sj.bjc.6600627
|View full text |Cite
|
Sign up to set email alerts
|

The LMCE5 unselected cohort of 25 children consecutively diagnosed with untreated stage 4 neuroblastoma over 1 year at diagnosis

Abstract: The Lyon-Marseille-Curie-Est (LMCE) of France cooperative group has previously reported successive series of unselected stage four children older than 1 year at diagnosis with metastatic neuroblastoma (LMCE 1 and 3). The goal of LMCE 5 study was to increase progression free survival rate as compared to LMCE 1 and 3. Based on improvements reported with post induction chemotherapy, the LMCE 5 used post induction for all children, but omitted total body irradiation and immunomagnetic purging in megatherapy regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…These studies evaluated megatherapy vs continuing intensive chemotherapy (Matthay et al, 1999), or maintenance chemotherapy (Berthold et al, 1990;Castel et al, 2001), or no treatment (Pritchard et al, 2005). Combined with the other experiences including megatherapy, they reliably support the conviction that this consolidation treatment modality offers an advantage in terms of survival probability (McCowage et al, 1995;Kushner et al, 2001;Frappaz et al, 2002;Kaneko et al, 2002;Kletzel et al, 2002;De Bernardi et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…These studies evaluated megatherapy vs continuing intensive chemotherapy (Matthay et al, 1999), or maintenance chemotherapy (Berthold et al, 1990;Castel et al, 2001), or no treatment (Pritchard et al, 2005). Combined with the other experiences including megatherapy, they reliably support the conviction that this consolidation treatment modality offers an advantage in terms of survival probability (McCowage et al, 1995;Kushner et al, 2001;Frappaz et al, 2002;Kaneko et al, 2002;Kletzel et al, 2002;De Bernardi et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…It is commonly accepted, but has not yet been convincingly confirmed within randomized trials, that rapid induction chemotherapy is more effective because the risk for neuroblastoma cells acquiring chemoresistance is considered to be lower. Chemotherapy regimens of the major US, European, Japanese and German neuroblastoma trial groups differ [9,10,24,30,33,40,50,82,102,105,126,148,149,151,155,195,198]. While data from controlled clinical trials comparing different induction chemotherapies are not yet available, response and outcome data from the previous GPOH high-risk neuroblastoma trials are similar to, or in some cases better than, those reported by other national neuroblastoma trial groups [9,123,149,154].…”
Section: Chemotherapymentioning
confidence: 85%
“…The number of available cytotoxic drugs effective for neuroblastoma is limited. Induction therapy for high-risk neuroblastoma patients worldwide consists of combinations of drugs including cisplatin, carboplatin, cyclophosphamide, ifosfamide, doxorubicin, etoposide, teniposide, vincristine and vinblastine [9,10,24,30,40,50,102,105,126,149,151,155,195,198]. One European randomized phase III trial compared rapid COJEC induction chemotherapy, which administers cytotoxic drugs every 10 days, to standard chemotherapy cycles administered every 21 days.…”
Section: Chemotherapymentioning
confidence: 99%
“…Intensive induction chemotherapy, myeloablative high-dose chemotherapy with autologous stem cell transplantation (ASCT), and surgery are accepted as important elements in the treatment of high-risk neuroblastoma [4,9,10,16,22,29]. External-beam radiation therapy (EBRT) proved effective in small series of localized neuroblastoma [7] and infants' neuroblastoma [24] but data in high-risk neuroblastoma are still limited [5,13,19].…”
Section: Introductionmentioning
confidence: 99%